2023
DOI: 10.1007/s10943-023-01967-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Physiological and Psychological Effects of Group Chanting in Australia: Reduced Stress, Cortisol and Enhanced Social Connection

Gemma Perry,
Vince Polito,
William Forde Thompson

Abstract: Chanting, an ancient ritual practiced in diverse cultures and traditions worldwide, has typically been employed for meditation, healing, self-awareness, and psychological growth. However, there is little understanding of the physiological and psychological benefits of chanting, and how vocalization might contribute to such effects. This study aimed to determine whether 12-minutes of group chanting, through vocal or silent repetition of the sound “om,“ would reduce stress and anxiety, while increasing feelings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Standardized Meditation (American Meditation Society) VH 1 Mantra integration Formal and informal use of Jesus Prayer (Knabb & Vazquez, 2018) X H 1 Mantra chanting Maha Mantra chanting (Wolf & Abell, 2003) X H 1 Islamic Dhikr (e.g., Roslan et al, 2022) V H ≥2 h Maha Mrtyunjaya Mantra chanting (Raghuwanshi et al, 2022) C 1 "Om" chanting (Perry et al, 2023) C 1 Kirtan Kriya (e.g., Moss et al, 2012) C 2…”
Section: Portable Mantra Repetitionmentioning
confidence: 99%
“…Standardized Meditation (American Meditation Society) VH 1 Mantra integration Formal and informal use of Jesus Prayer (Knabb & Vazquez, 2018) X H 1 Mantra chanting Maha Mantra chanting (Wolf & Abell, 2003) X H 1 Islamic Dhikr (e.g., Roslan et al, 2022) V H ≥2 h Maha Mrtyunjaya Mantra chanting (Raghuwanshi et al, 2022) C 1 "Om" chanting (Perry et al, 2023) C 1 Kirtan Kriya (e.g., Moss et al, 2012) C 2…”
Section: Portable Mantra Repetitionmentioning
confidence: 99%
“…This efficacy likely stems from the enhanced social interaction that singing encourages [49,55]. Studies have shown that engaging in singing and playing musical instruments triggers the release of several neurochemicals, including endorphins and dopamine, which are instrumental in regulating mood and enhancing feelings of pleasure by activating the reward system [56][57][58]. Moreover, singing can also reduce stress hormones such as cortisol [59,60], and singing, recognized for its participatory ease and accessibility, particularly in groups, leads to better quality of life and emotional well-being [9,61].…”
Section: Possible Interpretations Of Observationsmentioning
confidence: 99%